Perspektif Agama Buddha Dan Budaya Tionghoa Dalam Tradisi Perayaan Imlek Di Pontianak - Sunfu Sunfu; Rida Jelita; Hosan Hosan (Kajian dan Reviu Jinarakkhita: Jurnal Gerakan Semangat Buddhayana (Jinarakkhita Review & Studies: Journal of Buddhayana Spirit Movement), 2026)
This study examines the religious meaning of the Chinese New Year (Imlek) tradition among the Chinese community in Pontianak from the perspective of the Siṅgāla Sutta and the Maṅgala Sutta. While Imlek is commonly understood as a cultural tradition, empirical studies that interpret it through canonical Buddhist teachings remain limited. This research aims to analyze how Imlek practices reflect ethical and spiritual values within Buddhist teachings. A qualitative ethnographic approach was employed, with data collected through in-depth interviews, participatory observation, and document analysis involving community leaders, religious figures, and participants in Imlek celebrations. The findings indicate that, although Imlek is explicitly perceived as a cultural tradition, its practices embody implicit religious values. Social activities such as family gatherings, respect for elders, and communal participation reflect relational ethics consistent with the Siṅgāla Sutta. Meanwhile, practices such as almsgiving, sharing (angpao), and expressions of gratitude demonstrate moral and spiritual values aligned with the Maṅgala Sutta. The study reveals that Imlek can be understood as a form of culturally embedded religious practice, where Buddhist teachings are internalized through social and symbolic expressions rather than formal doctrinal articulation. This research contributes to Buddhist studies by proposing a sutta-based analytical framework to interpret local cultural practices, thereby bridging empirical traditions and canonical teachings in contemporary Buddhayana contexts.